2023
DOI: 10.1101/2023.03.17.533237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic interplay betweenProteus mirabilisandEnterococcus faecalisfacilitates polymicrobial biofilm formation and invasive disease

Abstract: Catheter-associated urinary tract infections (CAUTI) account for 40% of all nosocomial infections and can lead to significant life-threatening complications such as bacteremia. Microbial biofilms play an important role in the development and pathogenesis of CAUTI, and these biofilms are often polymicrobial. Proteus mirabilis and Enterococcus faecalis are two of the most common causes of CAUTI, and they often persistently co-colonize the catheterized urinary tract. We previously demonstrated that co-culture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Our data indicates that E. faecalis ATCC 29212, K. pneumoniae ATCC 9101, and S. epidermidis ATCC 51025 consumed the most arginine and generated the highest amounts of ornithine. Previous work has demonstrated that E. faecalis generated ornithine promotes other pathobionts (Hunt et al, 2023;Keogh et al, 2016;Smith et al, 2022). L-ornithine was found to stimulate enterobactin production and iron transfer in E. faecalis and uropathogenic E. coli polymicrobial biofilms (Keogh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data indicates that E. faecalis ATCC 29212, K. pneumoniae ATCC 9101, and S. epidermidis ATCC 51025 consumed the most arginine and generated the highest amounts of ornithine. Previous work has demonstrated that E. faecalis generated ornithine promotes other pathobionts (Hunt et al, 2023;Keogh et al, 2016;Smith et al, 2022). L-ornithine was found to stimulate enterobactin production and iron transfer in E. faecalis and uropathogenic E. coli polymicrobial biofilms (Keogh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Ornithine was specifically found to facilitate E. coli biosynthesis of the enterobactin siderophore, allowing E. coli growth and biofilm formation in iron‐limiting conditions that would otherwise restrict its growth. E. faecalis generated ornithine was also found to promote arginine biosynthesis in another gut pathobiont Proteus mirabilis (Hunt et al, 2023 ). To date, no studies have examined the cross‐talk of ornithine from K. pneumoniae or S. epidermidis on other bacteria, but studies in the future would be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, changes in the microbiome and metabolome can influence the severity of UTIs and the recovery process [ 22 , 100 ]. For instance, l-ornithine secretion by E. faecalis increases arginine production in P. mirabilis , a metabolic interaction that significantly reduces infection severity [ 125 ]. Microbial biofilms are critical in the origin and pathophysiology of catheter-associated UTIs.…”
Section: Interactions and Regulatory Relationships Between The Microb...mentioning
confidence: 99%